Analysis of differential metabolites during the secondary fermentation of Zhacai - LIU Yuling; REN Ting; ZHAO Zhiping; LUO Yuanli (Shipin yu jixie)
ObjectiveThis study aimed to investigate the changes of metabolites during the secondary fermentation process of Zhacai.MethodsAfter 6 months of salt-dehydrated pickled cabbage, the different metabolites before and after secondary fermentation were determined by liquid chromatography-tandem mass spectrometry (LC-MS/MS) combined with multivariate statistical analysis.Results147 different metabolites were screened after secondary fermentation, mainly including organic acids and their derivatives, organic heterocyclic compounds, lipids and lipid molecules, phenolic compounds, phenylpropane and polyketone compounds. Bitter amino acids (histidine, arginine, tyrosine and valine) down-regulated, lactic acid, acetic acid, phenylacetic acid, palmitic acid, linoleic acid, phenolic acid and other substances up-regulated. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis of the differential metabolites showed that Alanine, aspartate and glutamate metabolism, arginine and proline metabolism, and arginine biosynthesis were the most significantly correlated with the major differential metabolites.ConclusionAfter secondary fermentation, Zhacai have richer flavor substances, stronger aroma, and better taste.